Application of Focus Improvement to Reduce Non-Stick on Pad Problem in IC Packaging - Dharmalingam, Sivakumar (2004)
Total Productive Maintenance (TPM) methodologies are used to eliminate profit loss or waste due to equipment failure or defect. TPM is designed to get maximum efficiency from the equipment while creating a satisfactory working environment. In Motorola, Selangor yield improvement had been an important agenda. One of the TPM pillar which is Focus Improvement activity is designed to minimize targeted losses that had been carefully measured and evaluated, was employed to improve yield in front-end assembly. The top three yield lost in parts per million (ppm) were contributed by the following defects in descending order: Non Stick on Pad (2715 ppm), chip and crack (782 ppm) and missing wire (687 ppni). The team focused on Non Stick on Pad (NSOP). which was the top yield lost contributor. NSOP was due to: floating die, bonded ball small in size, foreign matter on pad and classifications to say a few. Floating die contributed 48% of the NSOP defect. In this project detailed